Western Australia Atropine for the Treatment of Myopia (WA‐ATOM) study: Rationale, methodology and participant baseline characteristics. (1st April 2020) - Lee, Samantha S.Y.; Mackey, David A.; Lingham, Gareth; Crewe, Julie M.; Richards, Michael D.; Chen, Fred K.; Charng, Jason; Ng, Fletcher; Flitcroft, Ian; Loughman, James J.; Azuara‐Blanco, Augusto; Logan, Nicola S.; et al.
Abstract: Importance: Atropine eyedrops are a promising treatment for slowing myopia progression in East Asian children. However, its effects on children in Australia, including those of non‐Asian background, have not been well‐studied. Background: The Western Australia Atropine for the Treatment of Myopia (WA‐ATOM) study aims to determine the efficacy and long‐term effects of low‐dose atropine eyedrops in myopia control. This paper describes the study rationale, methodology and participant baseline characteristics. Design: Single‐centre, double‐masked, randomized controlled trial. Participants: Children (6‐16 years) with spherical equivalent ≤−1.50 D in each eye, astigmatism ≤1.50 D and myopia progression by ≥0.50 D/year. Methods: Enrolled children were randomly assigned 2:1 to receive 0.01% atropine or placebo eyedrops. Participants are examined every 6 months during first 3 years of the study (2‐year treatment phase followed by a 1‐year washout phase), and then at a 5‐year follow‐up (2 years after the end of the washout phase). Main Outcome Measures: Annual progression rate of myopia and axial length, tolerability to eyedrops and incidence and severity of unwanted effects. Results: Out of 311 children who were referred, 242 were suitable for study participation, and 153 were subsequently enrolled. The baseline characteristics of enrolled participants are presented. Conclusions and Relevance: Outcomes of the WA‐ATOM study will inform on the efficacy, tolerability, safety and long‐term effects of low‐dose atropine eyedrops in myopia control in Australian children. The impact of ocular sun exposure, iris colour and parental myopia on the efficacy of low‐dose atropine will also be assessed.